2006
DOI: 10.1007/s10620-005-9062-4
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Randomized, Double-Blind, 8-Week Comparative Trial of Standard Doses of Esomeprazole (40 mg) and Omeprazole (20 mg) for the Treatment of Erosive Esophagitis

Abstract: To compare esomeprazole with omeprazole for healing erosive esophagitis (EE), 1148 patients with endoscopically confirmed EE were randomized to once-daily esomeprazole, 40 mg, or omeprazole, 20 mg, for 8 weeks in this multicenter, double-blind, parallel-group trial. The primary outcome was the proportion of patients with healed EE at week 8. Secondary outcomes included diary and investigator assessments of heartburn symptoms. At week 8, estimated healing rates were 92.2% (95% CI, 89.9%-94.5%) with esomeprazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 19 publications
2
47
0
Order By: Relevance
“…3b). Data on healing rate at 4 weeks were reported in 39 trials from 38 studies, 14,16,30,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] and the network for these comparisons was constructed with 18 treatments (vonoprazan, six PPIs, four H 2 RAs, and placebo) ( Fig. 3c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3b). Data on healing rate at 4 weeks were reported in 39 trials from 38 studies, 14,16,30,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] and the network for these comparisons was constructed with 18 treatments (vonoprazan, six PPIs, four H 2 RAs, and placebo) ( Fig. 3c).…”
Section: Resultsmentioning
confidence: 99%
“…For the sensitivity analyses, studies were excluded from the analysis as follows: one study 32 due to a high risk of bias from attrition, seven studies 35,38,39,45,48,65,68 that calculated healing rates based on PPS, and two studies 50,62 with only life table (or Kaplan-Meier) estimated healing rates. Only 20 studies (22 trials) 14,16,30,31,35,[37][38][39][40]42,43,[49][50][51]62,64,66,[68][69][70] used the Los Angeles scale for endoscopic assessment and were eligible for this analysis. The results (both estimates and orders) of these analyses were consistent with the main analysis, showing its robustness (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Several intragastric pH studies have shown that esomeprazole at a dose of 40 mg daily is superior to standard dosages of all other available original brand PPIs in controlling intragastric acidity, [3][4][5][6][7] while highdose esomeprazole was superior to high-dose pantoprazole in another study. 8 This functional superiority of esomeprazole is mirrored by significant clinical advantages over some other PPIs in healing and maintenance therapy of erosive GERD [9][10][11][12][13][14][15] whereas there were no differences when omeprazole was used in the treatment of non-erosive GERD. 16 Generic omeprazole has been approved and is being increasingly used for the treatment of GERD and other acid-related gastrointestinal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were considered healthy based on a detailed medical history, physical examination and routine laboratory assessment. Only subjects who were H. pylori-negative based on 13 C urea breath test (INFAI, Cologne, Germany) were eligible. Subjects with past or present significant illness and those with known intolerance to PPI were excluded.…”
Section: Subjectsmentioning
confidence: 99%
“…Proton pump inhibitors (PPIs) are the treatment of choice for both healing and maintenance therapy of RE (8)(9)(10). Numerous studies have demonstrated the efficacy of PPIs for initial healing of RE (11)(12)(13)(14)(15)(16)(17)(18) and numerous separate studies have demonstrated the efficacy of PPIs for maintaining endoscopic remission (8,10). The EXPO study (14,15), which compared esomeprazole with pantoprazole, is one of the few clinical trials to follow patients with RE through the entire course of management, i.e.…”
Section: Introductionmentioning
confidence: 99%